Understanding the Religious Rights of the Muslims in the Philippines: A Catalyst for Peace and Justice (Kefahaman tentang Hak Beragama Orang Islam di Filipina: Pemangkin untuk Keamanan dan Keadilan) - Tagoranao, Mariam Saidona; Gamon, Alizaman D. (Journal of Islam in Asia (E-ISSN 2289-8077), 2019)
Religious rights for minorities are not merely a privilege policy but an important commitment that should be acknowledged by any organization, state or nation. The contemporary legal systems of the world recognize religious rights particularly in today’s multicultural societies. This system has been acknowledged by the international law of human rights and the United Nations Conventions. Religious faith and religious practices are inherently protected by the Constitution of the Republic of Philippines. International law of human rights becomes the basis for a non-Muslim government to provide commitments in promoting spiritual and conventional infrastructures for Muslim minorities. The main objective of this paper is to discuss the national laws that can accommodate Muslim religious rights based on how Islam defines it, in order to achieve a lasting peace in the Philippines. The paper recommends that the universal principle of peace must be contained in the legal reform of every sovereign nation. In addition, religious obligations and liberties must be fairly treated and regarded as a national agenda towards promoting peace and justice. Keywords: Religious rights, Muslim minorities, Philippine Constitution, Peace and Justice. Abstrak Hak keagamaan untuk golongan minoriti bukan sekedar dasar keistimewaan semata, tetapi merupakan suatu komitmen penting yang harus diakui oleh mana-mana organisasi, negara atau bangsa. Sistem undang-undang kontemporari di dunia mengiktiraf hak beragama, khususnya dalam masyarakat pelbagai budaya hari ini. Ia telah diakui oleh undang-undang hak asasi manusia antarabangsa dan Konvensyen Pertubuhan Bangsa-Bangsa Bersatu. Kepercayaan dan amalan keagamaan pada dasarnya dilindungi oleh perlembagaan negara. Undang-undang ini menjadi asas bagi sebuah kerajaan bukan Islam untuk memberikan komitmen dan keprihatinan dalam mempromosikan infrastruktur rohani dan konvensional bagi golongan minoriti Muslim. Objektif utama kajian ini adalah untuk mengetahui sejauh mana undang-undang negara boleh menampung hak agama Islam berdasarkan bagaimana Islam mentakrifkannya, untuk mencapai keamanan yang kekal di Filipina. Keadaan menjadi amat malang apabila makna sebenar perdamaian akhirnya terhakis akibat penyelewengan yang lazimnya berlaku dalam sistem dan amalan perundangan. Walau bagaimanapun disyorkan, bahawa prinsip sejagat kedamaian mesti terkandung dalam reformasi undang-undang bagi setiap negara berdaulat. Di samping itu, kewajipan dan kebebasan beragama mesti dilayan dengan adil dan dianggap sebagai agenda nasional untuk mempromosikan keamanan dan keadilan. Kata Kunci: Hak keagamaan, minoriti Islam, Perlembagaan Filipina, Keamanan dan Keadilan.